2011
DOI: 10.1021/la2018083
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contact Angles and Hysteresis under Electrowetting-on-Dielectric

Abstract: By designing and implementing a new experimental method, we have measured the dynamic advancing and receding contact angles and the resulting hysteresis of droplets under electrowetting-on-dielectric (EWOD). Measurements were obtained over wide ranges of applied EWOD voltages, or electrowetting numbers (0 ≤ Ew ≤ 0.9), and droplet sliding speeds, or capillary numbers (1.4×10-5 ≤ Ca ≤ 6.9×10-3). If Ew or Ca is low, dynamic contact angle hysteresis is not affected much by the EWOD voltage or the sliding speed, i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 45 publications
2
55
2
Order By: Relevance
“…CAH is also sensitive to the volume fraction of the microbead suspension [14]. Experiments on CAH were carried out under various situations such as electrowetting-on-dielectric [15] and asymmetric vibration [16]. Recently, Bormashenko et al presented an ingenious experimental technique to measure CAH based on the slow deformation of the droplet [3].…”
Section: Introductionmentioning
confidence: 99%
“…CAH is also sensitive to the volume fraction of the microbead suspension [14]. Experiments on CAH were carried out under various situations such as electrowetting-on-dielectric [15] and asymmetric vibration [16]. Recently, Bormashenko et al presented an ingenious experimental technique to measure CAH based on the slow deformation of the droplet [3].…”
Section: Introductionmentioning
confidence: 99%
“…Wyatt C. Nelson et al have studied the dynamic contact angle and hysteresis under electrowetting-on-dielectric. 7 Measurements show that if E w or Ca (capillary number) is low, dynamic contact angle hysteresis is not affected by the EWOD voltage or the sliding speed; that is, the hysteresis increases by less than 50% with a 2 order-of-magnitude increase in sliding speed when Ca < 10 −3 . If both E w and Ca are high, the hysteresis increases with either the EWOD voltage or the sliding speed.…”
Section: The Theoretical Basis Of Ewodmentioning
confidence: 96%
“…Strong elastic bonds are applied at the surface with sixteen atom molecules used to hold the liquid region together and prevent evaporation with Tanner's law and MKT also reproduced by the presented results. Experimental studies of liquid bridges also provide some insight into the general behaviour where the study of Wang and McCarthy 20 observed pinch off while Nelson et al 21 studied the angle sliding rate dependence in the presence of electrowetting.…”
Section: Introductionmentioning
confidence: 99%